GAYA BAHASA TUNG DESEM WARINGIN DALAM SEMINAR FINANCIAL REVOLUTION DAN RANCANGAN PEMBELAJARANYA - Fitri Nursilawati; Munaris Munaris (FKIP Universitas Lampung, 2016)
The research problems in this research was about the design of four elements of style (diction, sentence structure, tone, direct or indirect sense) in Tung Desem Waringins seminar entitled financial revolution as teaching learning material of Indonesian language and literature at first year student of senior high school. This research aimed to describe the program of those four elements of language style as the language learning material in senior high school. The research method in this research was descriptive qualitative research design. The results of the research showed that the foreign diction was dominated by the England diction. Figurative language was dominated by the sentence structure of figurative language in which epizeuksis repetition took the first place in figurative language usage. Meanwhile, antiklimaks, asidenton, paradoks, erotesis, came as the less usage of figurative language. Style in this financial revolution seminar was style in diction, sentence structure, tone, and direct or indirect sense.Masalah yang dibahas dalam penelitian ini adalah bagaimana gaya bahasa Tung Desem Waringin dalam seminar financial revolution dan rancangannya sebagai bahan ajar bahasa Indonesia di SMA. Tujuan penelitian ini untuk medeskripsikan empat gaya bahasa Tung Desem Waringin dalam seminar financial revolution dan rancangannya sebagai bahan ajar bahasa Indonesia di SMA. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa penggunaan diksi asing didominasi oleh diksi yang berasal dari bahasa Inggris. Gaya bahasa berdasarkan struktur kalimat didominasi oleh gaya repetisi epizeuksis. Gaya bahasa yang paling sedikit digunakan antiklimaks, asidenton, paradoks, erotesis. Gaya bahasa dalam seminar financial revolution ini meliputi gaya bahasa berdasarkan diksi, struktur kalimat, nada, dan langsung atau tidaknya makna.Kata kunci: seminar financial revolution, gaya bahasa, rancangan pembelajaran